2018
DOI: 10.1111/nmo.13378
|View full text |Cite
|
Sign up to set email alerts
|

Systemic cytokines are elevated in a subset of patients with irritable bowel syndrome but largely unrelated to symptom characteristics

Abstract: Serum cytokines are elevated in IBS patients compared to HS. Immune activation characterizes a subset of patients, but modest associations between cytokine profile and symptoms suggest immune activity does not directly influence symptoms in IBS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 56 publications
5
17
0
Order By: Relevance
“…This approach identified a subset of IBS patients (33%), referred to as immuno‐active IBS, with evidence of increased immune activation in the colon descendens . These results are in line with previous studies showing increased immune activation in a subset of Swedish IBS patients based on multivariate analysis of serum levels and mucosal expression of a small set of 5 and 9 cytokines, respectively. To further evaluate the potential role of immune activation in IBS, we compared the clinical characteristics of immuno‐active vs immuno‐normal IBS patients.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This approach identified a subset of IBS patients (33%), referred to as immuno‐active IBS, with evidence of increased immune activation in the colon descendens . These results are in line with previous studies showing increased immune activation in a subset of Swedish IBS patients based on multivariate analysis of serum levels and mucosal expression of a small set of 5 and 9 cytokines, respectively. To further evaluate the potential role of immune activation in IBS, we compared the clinical characteristics of immuno‐active vs immuno‐normal IBS patients.…”
Section: Discussionsupporting
confidence: 92%
“…To further evaluate the potential role of immune activation in IBS, we compared the clinical characteristics of immuno-active vs immuno-normal IBS patients. In line with two previous Swedish studies, 33,41 no differences in clinical symptoms could be identified between these two subgroups, suggesting no direct relationship between mucosal low-grade inflammation, assessed by gene expression analysis, and symptoms in IBS. However, previous clinical trials in IBS have reported clinical improvement with the mast cell stabilizer ketotifen 30 and the histamine 1 receptor antagonist ebastine 42 while a subgroup of IBS patients seems to respond to treatment with mesalazine.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…IBS is not an inflammatory disease as such, but growing evidence suggests that dysregulation in immune function is associated with at least a subgroup of IBS patients and could contribute to either etiology or symptoms (21,(120)(121)(122)(123)(124)(125).…”
Section: Immune Activation In Ibsmentioning
confidence: 99%